5x+7-3x=3x+12

Simple and best practice solution for 5x+7-3x=3x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+7-3x=3x+12 equation:


Simplifying
5x + 7 + -3x = 3x + 12

Reorder the terms:
7 + 5x + -3x = 3x + 12

Combine like terms: 5x + -3x = 2x
7 + 2x = 3x + 12

Reorder the terms:
7 + 2x = 12 + 3x

Solving
7 + 2x = 12 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
7 + 2x + -3x = 12 + 3x + -3x

Combine like terms: 2x + -3x = -1x
7 + -1x = 12 + 3x + -3x

Combine like terms: 3x + -3x = 0
7 + -1x = 12 + 0
7 + -1x = 12

Add '-7' to each side of the equation.
7 + -7 + -1x = 12 + -7

Combine like terms: 7 + -7 = 0
0 + -1x = 12 + -7
-1x = 12 + -7

Combine like terms: 12 + -7 = 5
-1x = 5

Divide each side by '-1'.
x = -5

Simplifying
x = -5

See similar equations:

| 3(9.99)+5(1.29)= | | r(x)=2x-0.03x^2 | | 4y-2x-12=0 | | 4(p+5)=48 | | 78/x | | 0x+10y=-10 | | 48x^2=27x | | x+x+1+10=1 | | 0x+10y=0 | | 10x+1y=270 | | 3(-9+2z)-18z=-15 | | 20+-30= | | F(x)=x^2-4x+19 | | 2x^2-2x-12=7 | | 3(x+3)+x+2(3x+1)= | | 13s+4=-3(3-4s)-1 | | 140+25x=140+25x | | 0x+6y=-24 | | 2ln(x)+3=9 | | 75(3/4) | | F(x)=1x^2+2x+2 | | 9x-14=52 | | 4(2n+3)=7(4n+1)+9 | | 6+y=14-3y | | x+3(3x+1)+x+9= | | 48-2y=4y | | x^(-1/13)=1/2 | | 3sin(2x-1)-1=0 | | Y=9.25*6x | | x^(-1/13=1/2 | | 27m^2+36m+12= | | 5i=15u |

Equations solver categories